2005
DOI: 10.1073/pnas.0500329102
|View full text |Cite
|
Sign up to set email alerts
|

Pooled association genome scanning: Validation and use to identify addiction vulnerability loci in two samples

Abstract: Association genome scanning is of increasing interest for identifying the chromosomal regions that contain gene variants that contribute to vulnerability to complex disorders, including addictions. To improve the power and feasibility of this approach, we have validated ''10k'' microarray-based allelic frequency assessments in pooled DNA samples and have used this approach to seek allelic frequency differences between heavy polysubstance abusers and well characterized control individuals. Thirty-eight loci con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
114
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 90 publications
(118 citation statements)
references
References 47 publications
4
114
0
Order By: Relevance
“…Such observations also come from the 10k data displayed in Table 1. 35 Neurexin 3 is a cell adhesion gene 37 and the AIP1 (atrophin interacting protein 1) gene, which is also known as S-SCAM (subcellular scaffolding cell adhesion molecule), plays a role in helping to anchor and localize the neurexin 3 ligand, neuroligin. 38 Thus, even this modest-density SNP genome scan has identified two of the gene products that participate in one of the major cell adhesion events that helps to specify excitatory versus inhibitory synapse formation and/or maintenance.…”
Section: The Scope Of Current Molecular Genetic Data For Addictionsmentioning
confidence: 99%
“…Such observations also come from the 10k data displayed in Table 1. 35 Neurexin 3 is a cell adhesion gene 37 and the AIP1 (atrophin interacting protein 1) gene, which is also known as S-SCAM (subcellular scaffolding cell adhesion molecule), plays a role in helping to anchor and localize the neurexin 3 ligand, neuroligin. 38 Thus, even this modest-density SNP genome scan has identified two of the gene products that participate in one of the major cell adhesion events that helps to specify excitatory versus inhibitory synapse formation and/or maintenance.…”
Section: The Scope Of Current Molecular Genetic Data For Addictionsmentioning
confidence: 99%
“…3 Candidate gene studies and linkage-based genome scans have identified multiple chromosomal regions as sources of potential susceptibility to AD as well as other addictions, showing some convergent findings. 4 Examples of this convergence are the genes encoding alcohol dehydrogenase IB (ADH1B) and aldehyde dehydrogenase 2 (ALDH2), which were originally based on the mechanism of the association of ADH1B and ALDH2 polymorphisms with AD in that the isoenzymes encoded by these alleles lead to an accumulation of acetaldehyde during alcohol metabolism. In other investigations of interest to the current study, cigarette smoking with or without AD, were linked to broad regions of chromosomes 9 and 11.…”
Section: Introductionmentioning
confidence: 99%
“…In other investigations of interest to the current study, cigarette smoking with or without AD, were linked to broad regions of chromosomes 9 and 11. [4][5][6][7][8][9] Among the candidate addiction susceptibility genes defined by these linkage signals were those that encode the neurotrophin, brainderived neurotrophic factor (BDNF, chromosome 11), and its cognate receptor, neurotrophic tyrosine kinase receptor B (TrkB) (NTRK2, chromosome 9).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is likely that in the future a panel of genetic markers, or even a whole-genome scan, will form the basis of treatment tailoring, potentially leading to a stronger benefit of tailored therapy. 29,48 Third, the effects of discounting across time and the modest survival benefits of increasing the 6-month quit rate lead to clustering of the mean cost and LY outcomes, and consequently our comparisons are sensitive to model parameters and assumed costs when varied in combination. In some cases, the differences between treatments were too small to distinguish statistically even with the large number of subjects we simulated, leading to ambiguity in the determination of which treatments are dominated.…”
Section: Discussionmentioning
confidence: 99%